PROTECTION FOR CHILDRENS OF VICTIM OF THE TERRORISM CRIME UNDER THE CRIMINAL LAWS (A BASIC EXAMINATION TO THE NEW LAW PROTECTION FOR THE VICTIMS AND WITNESS) - Dian Narwastuty (Hukum Pidana dan Pembangunan Hukum, 2018)
The development of protection for victim in Indonesia has grown to a new stage. These developments also develop the protection for the children that involved in terrorism crime. The Surabaya Church’ terror, The Polrestabes’s Case, etc has showed that the terrorism involved children as active doer. Identification: There should be new form of protection, especially for the children of terrorism victim crime. Method :This paper uses qualitative descritive methods that regarding the new rules of Protection For Victims and Witness which enriched by library approach. The primary data is law’s protection around Victim and Witness, The secondary data are the form of books and  journals  about Criminal’s Law. The finding :The main project to avoiding the children became a terrorism victims is to restricted the radical ideology in internet . Keywords: Law, Protection, Children, Terrorism, Victims, Witness.